The Role of Faculty Members’ Practices (Academic Motivating and Skill Development) in Enhancing Students’ Motivation to Learn A Survey Study of Students at the University of Latakia (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This Study aims to examine the role of faculty members’ practices—specifically motivating and skill development—in enhancing students’ motivation to learn from the perspective of students at the University of Latakia. The researcher adopted an analytical approach, utilizing a survey method and relying on simple random sampling to collect data. A structured questionnaire was developed and administered to a sample of 420 students; however, 30 questionnaires were excluded due to invalidity of the responses. The study population consisted of undergraduate students enrolled in the 2024–2025 academic year, totaling 67,182 students, according to the Directorate of Statistics and Planning. Appropriate statistical techniques, including simple linear regression, were employed using the SPSS software to analyze the collected data.The findings revealed several key results, most notably the statistically significant effect of faculty members’ practices (motivating and skill development) on enhancing students’ motivation to learn. The level of faculty contribution to motivating students and developing their skills was moderate, whereas the overall level of students’ motivation to learn was high. Furthermore, no statistically significant differences were identified in students’ evaluations of faculty members’ roles attributable to the faculty (college) or academic year. Based on these findings, several recommendations were proposed, the most important of which was the development of a professional training program for faculty members. Such a program should include semester-based workshops focusing on strategies to motivate students and foster 21st-century skills.
Keywords: Motivating; Skill Development; Students’ Learning Motivation; University of Latakia.